Comparison of Repetitive Transcranial Magnetic Stimulation and Transcranial Direct Current Stimulation on Upper Limb Recovery Among Patients With Recent Stroke - Ka Ying Doris Miu; Ching Kok; Sau Shan Leung; Elaine Y. L. Chan; Elaine Wong (Annals of Rehabilitation Medicine, 2020)
Objective To compare the efficacy of repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) on upper limb function recovery among patients who recently had stroke. Methods Subjects with recent stroke (within 1 month) were randomized to rTMS (n=25) and tDCS (n=26) applied over the non-lesioned hemisphere for three sessions per week, followed by tailored upper limb rehabilitation training for a total of 2 weeks. The primary outcomes were changes in the Motor Assessment Scale (MAS), Fugl-Meyer arm score test, Nine-Hole Peg Test (9HPT), hand grip strength, and modified Barthel Index at weeks 2 and 4. Both therapists responsible for training and assessment were blinded to the intervention allocated. Results There was an improvement in all the motor performance scales among both groups (p<0.001). These improvements persisted at discharge. However, there was no significant difference in any of the assessment scales between the two groups. The rTMS group showed a statistically non-significant greater improvement in MAS, 9HPT, and handgrip strength than the tDCS group. Conclusion Both interventions produce a statistically significant improvement in upper limb function. There was no statistically significant difference between the two intervention methods with respect to motor performance. It is suggested that a larger study may help to clarify the superiority of either methods.